Association Study Reveals Novel Genes Related to Yield and Quality of Fruit in Cape Gooseberry (Physalis peruviana L.) - García-Arias, Francy L.; Osorio-Guarín, Jaime A.; Núñez Zarantes, Victor M. (Frontiers in Plant Science, 2018)
Association mapping has been proposed as an efficient approach to assist plant breeding programs to investigate the genetic basis of agronomic traits. In this study, we evaluated 18 traits related to yield, (FWP, NF, FWI and FWII), fruit size-shape (FP, FA, MW, WMH, MH, HMW, DI, FSI, FSII, OVO, OBO) and fruit quality (FIR, CF and SST), in a diverse collection of 100 accessions of Physalis peruviana including wild, landraces and anther culture derived lines. We identified seven accessions with suitable traits: fruit weight per plant (FWP) > 7,000 g/plant and cracked fruits (CF) < 4%, to be used as parents in cape gooseberry breeding program. In addition, the accessions were also characterized using Genotyping By Sequencing (GBS). We discovered 27,982 and 36,142 informative SNP markers based on the alignment against the two cape gooseberry references transcriptomes. Besides, 30,344 SNPs were identified based on alignment to the tomato reference genome. Genetic structure analysis showed that the population could be divided into two or three sub-groups, corresponding to landraces-anther culture and wild accessions for K=2 and wild, landraces and anther culture plants for K=3. Association analysis was carried out using a Mixed Linear Model (MLM) and 34 SNP markers were significantly associated. These results reveal the basis of the genetic control of important agronomic traits and may facilitate marker-based breeding in Physalis peruviana.